Wpływ polityki i prawodawstwa Unii Europejskiej na kształtowanie się polskiej regulacji prawnej w zakresie energetyki odnawialnej - Wójcik, Anna (Kwartalnik Prawa Publicznego, 2017)
The aim of the article is an attempt to analyze Polish legal regulation and mechanisms supporting renewable energy industry, which are expression of direct influence of the European Union policy and legislation in the times of shaping the Polish renewable energy sources market. The 2013 amendment of the Polish law, known in the literature as „the small energy tri-pack”, has become a response to a growing need to reform and modernize the energy sector based on fossil fuel. The „small energy tri-pack” has introduced some legal regulations which constituted the beginning of the development of the Polish renewable energy sources market.